EFEKTIFITAS PENYULUHAN KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN MASYARAKAT TENTANG PENCEGAHAN DEMAM BERDARAH DENGUE DI WILAYAH KERJA PUSKESMAS PESANGGRAHAN KABUPATEN MOJOKERTO - Kadek Gede Dhiyo Bhargo Yasa; Atik Sri Wulandari; Wike Herawaty; Rani Nur Rafli Amalia; Niken Triyulianita S; Lailatul Jannah; Aflacha Alivia Risalatul I; Ni Putu Santhi Cahya Dewi; Kadek Rio Risnanda; I Komang Adhi Arya Yudanta; Sukma Sahadewa (PT. Hasba Edukasi Mandiri, 2026)
Dengue Hemorrhagic Fever (DHF) is an acute infectious disease that remains a public health problem in Indonesia, particularly in tropical areas with high population density. Community-based prevention efforts through health education are essential to reduce the incidence of DHF. This community service activity aimed to improve knowledge, awareness, and preventive behaviors regarding DHF through health education for residents of Kenjoro Hamlet, Pesanggrahan Village, Mojokerto Regency. The target participants were mothers or parents of children aged 0–5 years and the elderly, who are vulnerable groups to DHF infection and complications. The method used was participatory health education employing booklet media, discussions, question-and-answer sessions, and evaluation through pre-test and post-test questionnaires. The material covered the definition, risk factors, transmission, signs and symptoms, management, and prevention of DHF through the Mosquito Breeding Site Eradication Program (PSN) 3M Plus. The activity was conducted on February 13, 2026, with 26 participants. Evaluation results showed a significant increase in knowledge, indicated by the proportion of correct answers rising from 50% in the pre-test to 95% in the post-test. In addition, several environmental risk factors were identified, such as stagnant water, uncovered water storage containers, and discarded items that could serve as mosquito breeding sites. In conclusion, health education effectively improved community knowledge and awareness regarding DHF prevention and encouraged the adoption of clean and healthy living behaviors through the 3M Plus program. Similar activities need to be conducted continuously with support from community health centers, village authorities, and active community participation to reduce the risk of DHF transmission.